Mutagenic activity of airborne particulate matter (PM10) in a sugarcane farming area (Araraquara city, southeast Brazil) - de Andrade, Sandro Jose [UNESP]; Varella, Soraya Duarte [UNESP]; Pereira, Gener Tadeu [UNESP]; Zocolo, Guilherme Juliao [UNESP]; Rodrigues de Marchi, Mary Rosa [UNESP]; Varanda, Eliana Aparecida [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
Brazil contains 25% of the total land planted with sugarcane in the world and is thus one of the major producers. The annual burning of sugarcane fields prior to harvesting emits huge amounts of pyrogenic particles. Biomass burning is an important primary and secondary source of aerosol particles. The presence of carbonaceous particles in the inhalable size range makes it important to study this fraction in view of the possible effects on human health and the climate. In this study, the mutagenic activity associated with inhalable airborne particulate matter (PM10) collected on air filters in a sugarcane-growing area near the city of Araraquara (SE Brazil) was determined. The extracts were dissolved in dimethylsulfoxide and tested for mutagenicity by the Ames plate incorporation test with Salmonella typhimurium YG1024 in the presence and absence of the S9 mixture. To assess the association between mutagenicity and PM10, samples were collected in sugarcane harvesting and non-harvesting periods of the year. Significant mutagenicity was detected in organic solvent extracts of all samples, with differences between the two periods. The highest values of mutagenic potency (13.45 and 5.72 revertants/m(3) of air in the absence and presence of the S9 mixture, respectively) were observed during the harvest. In this period, a Teflon (TM)-coated glass-fiber air filter trapped 67.0 mu g of particulate matter per m(3) of air. In the non-harvest period, on the same type of filter, only 20.9 mu g of particulate matter was found per m(3). The mutagenic potencies at this time were 1.30 and 1.04 revertants/m(3) of air, in the absence and presence of the S9 mixture, respectively. Period, concentration of PM10 and mutagenicity were associated with each other. For routine monitoring of mutagenicity in the atmosphere, the use of YG1024 tester strain without metabolic activation (S9) is recommended. (c) 2011 Elsevier B.V. All rights reserved.
Keywords: Mutagenicity of airborne particulates; Ames test; YG1024 strain; PM10; Sugarcane